2014
DOI: 10.1371/journal.pone.0095082
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Utility of fMRI for Identifying Covert Awareness in the Vegetative State: A Comparison of Sensitivity between 3T and 1.5T

Abstract: In the last few years, mental imagery fMRI paradigms have been used successfully to identify covert command-following and awareness in some patients who are thought to be entirely vegetative. However, to date there is only evidence supporting their use at magnetic fields of 3T, which limits their applicability in clinical settings where lower field strengths are typically used. Here, we test the ‘gold standard’ fMRI paradigm for detecting residual awareness in non-responsive patients by comparing its sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 24 publications
3
61
0
1
Order By: Relevance
“…However, the fMRI timecourse for this subject was similar to the other subjects and did not indicate inverse oxygenation, and hence this result warrants further investigation. As for the 3 subjects with no detectable fMRI or fNIRS activity, this is not uncommon and similar results have been reported previously in the literature 5 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, the fMRI timecourse for this subject was similar to the other subjects and did not indicate inverse oxygenation, and hence this result warrants further investigation. As for the 3 subjects with no detectable fMRI or fNIRS activity, this is not uncommon and similar results have been reported previously in the literature 5 .…”
Section: Discussionsupporting
confidence: 90%
“…The motor imagery experimental protocol used in this study was previously described elsewhere 5 , which consisted of five cycles of 30 seconds alternating blocks of rest and tennis imagery, with a total experiment time of five and half minutes. The two cue words used in this study were "rest" and "tennis".…”
Section: Measurement Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results confirm those of Fernandez-Espejo in which the protocol has been realized at 1.5T and 3T providing similar patterns of activations at the group level but with a non-systematic activation of ROIs at the individual level (Fernandez-Espejo et al, 2014). Before being offered as standard clinical care in a unit, fMRI paradigms used to study volitional brain activity in DOC patients first have to be validated on cohorts of healthy volunteers.…”
Section: Discussionsupporting
confidence: 82%
“…However, although other studies have successfully reproduced similar activations at the group level using this paradigm of detecting cerebral activity modulation on aware subjects (Aslaksen et al, 2012, Liang et al, 2014, the robustness of this paradigm (on aware subjects) has yet to be confirmed at the individual level. Indeed, if the healthy controls recruited in the seminal works of Boly (Boly et al, 2007), Monti (Monti et al, 2010) and Owen (Owen et al, 2006) activated the SMA during motor imagery and the PPA during spatial imagery, a recent article from the same team (Fernandez-Espejo et al, 2014) could not replicate such a result. In that study, at best 85.7% of healthy subjects activated the SMA during motor imagery, and at best 57.1% activated the PPA during spatial imagery.…”
Section: Introductionmentioning
confidence: 99%